Optimization of Cellulase Enzyme Production from Corn Cob Waste by Cellulolytic Fungus Aspergillus niger - Yuliandini, Sinta; Peristiwati, Peristiwati; Surakusumah, Wahyu (Mahesa Research Center, 2025)
Corncob is an agricultural waste rich in cellulose, making it a promising alternative substrate for cellulase enzyme production, which is widely used in various industrial applications such as bioenergy, food, and textile industries. Aspergillus niger is a well-known cellulolytic fungus capable of efficiently producing cellulase enzymes. This study aimed to optimize cellulase production by A. niger using corncob powder (Zea mays) as a substrate through submerged fermentation (SmF), with variations in temperature (29.5°C and 30.5°C) and pH (4.5 and 5.5). The cellulolytic activity of A. niger was tested on CMC agar medium. Cellulase activity was analyzed based on the concentration of reducing sugars using the DNS method. The highest enzymatic activity was recorded at 1.125 IU/mL with a biomass yield of 0.754 mg/mL at 30.5°C and pH 4.5. These findings suggest that optimizing environmental conditions and utilizing corncob waste as a carbon source can enhance cellulase production by A. niger, offering a sustainable and cost-effective approach for enzyme-based industries.